Renal Cortical Thickness in Adult with Normal Renal Function Measured by Ultrasonography - Sah, Dambar; Md. Kalim Akthar,; Akhilesh Kumar Jha,; Shashi Shekhar Prasad Singh,; Rajan Kumar Mahato,; Bikranta Rimal,; Chandan Chaurasiya,; Rakesh Kumar Jha,; Trayush Adhikari,; Ajay Kumar Gupta, (Med Phoenix, 2023)
Introduction: Renal cortical thickness is an important parameter for many renal pathologies. Ultrasonography has been an efficient tool for the measurement of different renal parameters. The objective of this study was to determine the renal cortical thickness in healthy adults without any renal impairments and to correlate it with age, sex, height, weight, BMI and side of the body. Materials and Methods: A total of 150 healthy adults with normal renal function were included in this study. A detailed clinical history of all the patients were taken. Basic investigations, clinical and ultrasonography examination were performed. Informed written consent and ethical approval were taken. Results: The study included 150 participants (67 male & 83 female) with mean age of the participants 33.0±9.5 years. The mean renal cortical thickness was found to be 8.3±0.69mm. There was significant correlation between RCT and gender (p=0.013). However, no such correlation was observed between (renal cortical thickness) RCT and age, height, weight and BMI of the participants. Conclusion: Ultrasonographic measurement of renal cortical thickness plays a vital role in identification of many renal diseases. Thus, the result of this study can be used for evaluation of renal cortical thickness to determine abnormal renal conditions.